The Six-Minutes Walking Test (6MWT) in healthy Turkish children and its comparative review - Asli Sahın; Aysegul Aksoy; Baris Karakoyun; Gulsah Sahın; Hasim Katra; Kubra Gultekın; Nevin Kaya; Nurdan Yaykın; Omer Durukan; Omur Kocak; Ozan Canpolat; Ozhan Bavlı; et al. (Selcuk University, 2014)
Having  data about its own subjective condition is important for each country. The aim of this study was to establish the values for six-minutes walking test (6MWT) among healthy children.  The study population included 732 children (342 girls and 390 boys) aged 7-14 from 3 different regions in the city center. Their height and weight were measured and  a six-minutes walking test was performed to the children. Mann-Whitney U test for gender and walking distance; Pearson correlation test for the relationship between height, weight and age; Kruskal-Wallis analysis methods for walking distance of the age groups were used. The six-minutes walking (6MWT) distance of the children ages 7-14 was 684.20 ± 109.31 m in total. There was significantly positive relation in medium level between children's age and the 6MWT distance. There was a significantly positive relation in medium level between children's height and the 6-MWT distance. There was also a significantly positive relation in low level between children's weight and the 6-MWT distance. A statistically significant difference between the 6-MWT distance according to children's gender was observed. Finally there was a significant difference between 6-MW distance according to the children's age groups.